Shiʿi Theology and Polemics between Iran and India: The Case of Saiyed Nūrollāh Šūštarī (d. 1019/1610) - Rizvi, Sajjad (Entangled Religions, 2022)
Connected intellectual history is one of the modes in which we can consider the ways in which ideas, theologies and even polemical exchanges travel between different geographical and political milieux. In this case study, I examine the theology and polemics of Saiyed Nūrollāh Šūštarī between his birth and intellectual formation in eastern Iran and his career and eventual death at the Mughal court. I indicate how his polemical works played a role in transmitting theological ideas and debates from the Iranian milieu to Indian scholarly circles, and how the fluctuating fortunes and reception of his work followed the political shifts and patronage at court.